M. Roger Léonard en visite au M’zab (La vigie marocaine, 1952)
ALGER. 21 avril (P.P ). — A l’occasion des fêtes du Chouffane. M Roger Léonard, gouverneur général de l’Algérie, vient de passer deux Jours au Mzab, Dans un discours prononcé â Beni-Inchen. Il a déclaré qu'il estimait possible d’apporter une solution au problème de l'eau, particulièrement dans le domaine de l’irrigation, et souligne l’Importance que représente pour l'équilibre économique de l’Algérie l’exode périodique des populations mozabltes vers le Nord.
Keywords: Emigration -- Mzab -- Algérie

Migration, Commerce and Community: the Mīzābīs in Nineteenth-Century Algeria - Holsinger, Donald C. (Northwestern University, 1979)
Keywords: Emigration -- Mzab -- Algérie

Muslim Responses to French Imperialism: An Algerian Saharan Case Study - Holsinger, Donald C. (The International Journal of African Historical Studies, 1986)
The political events that preceded French occupation of Mīzāb, based mainly on French archivial materials. The awkward position of the Mīzābīs between French superior military power, which could easily destroy their trading activities in the North if they would not submit to French demands, and the threat of attaques on them by rebels in the South and their nomadic supporters if they would openly submit to the French and support them. This dilemma led to fierce internal strife in Mīzāb.
Keywords: Emigration -- Mzab -- Algérie

Migration, Commerce and Community: the Mīzābīs in Eighteenth-and Nineteenth-Century Algeria - Holsinger, Donald C. (The Journal of African History, 1980)
The Mīzāb is an Ibādī community consisting of seven cities clustered in an arid rocky region 350 miles south of Algiers. Having established these settlements nearly a millennium ago, the Mīzābīs, as the inhabitants came to be known, struggled against formidable environmental odds and managed not only to survive but to prosper. By the sixteenth century the Mīzāb had become an important northern Saharan market. During the following centuries, the Maghrib witnessed a remarkable movement of Mīzābī men to coastal cities where they attained prominence in a variety of professions while leaving their roots firmly implanted within their distant oasis community. Following a brief historical background to settlement in the Mīzāb, this article sketches the ecological constraints of an urban community in a region virtually devoid of resources. It then traces the history of the commercial dispersion to the North during the eighteenth and nineteenth centuries and discusses the probable causes of emigration. The Mīzābīs were forced by environmental constraints to seek outside sources of support. Their rise to prominence in the Regency of Algiers may have been related to declining Saharan commerce and new commercial opportunities in the North. The organization and function of Mīzābī corporations in Algiers and other northern cities are described. Finally, this article relates an Ibāçī reform ethic to Mīzābī commercial success and concludes with some reflections on religious ideology and environmental demands as contributing factors to the long-term Mīzābī role in commerce.
Keywords: Emigration -- Mzab -- Algérie

Trade routes of the Algerian Sahara in the nineteenth century - Holsinger, Donald C. (Revue de l'Occident musulman et de la Méditerranée, 1980)
A study of the impact of French imperialism on northern Saharan trade. Mīzāb’s important role in this trade
Keywords: Emigration -- Mzab -- Algérie

Quelques documents sur la corporation des Mozabites d’Alger dans les premiers temps de la conquête (1830-1838) - Lespès, René (Revue Africaine, 1925)
A critical study with reference to a letter of Mīzābīs in Algiers to the commander of the French occupying forces intended to keep the priviliges they had acquired under the Turks.
Keywords: Emigration -- Mzab -- Algérie

Thalāthu Rasā’il Makhṭūṭa ḥawla al-Ibāḍiyya al-Mīzābiyyīn bi’l-Jazā’ir fī ‘l-ʿAhd al-ʿUthmānī - Baḥḥāz, Ibrāhīm (Revue d'Histoire Maghrébine, 1998)
The Ottoman period in Algeria was from 1515-1830. These three letters are from the private library of Muḥ. al-Ḥājj Saʿīd b. Ayyūb in Ghardaïa, Mīzāb. The first letter (Dhū ‘l-Qaʿda 1206/1792) contains a complaint from the Mīzābīs to the Dāy Bābā Ḥasan (1791-1798) about the intention of Ṣāliḥ Bāy, Bāy of Constantine (1771-1792), to subdue the Mīzābīs and their families, to lead their women and children into captivity, and subsequently to exterminate them, probably for no other reason then their belonging to the Ibāḍī Madhhab. The second letter (Muḥarram 1207/Aug. 1792) is a letter of thanks for the Dāy’s help. The third one (end of Ṣafar 1207/1792), to al-Ḥājj ʿAlī b. ʿAbd al-Laṭīf, Siḥr of the Dāy and their mediator with the Dāy, “expresses the acknowledgment of what is beautiful by its writers”; it contains the aforementioned complaint and the Mīzābīs’ gratitude.
Keywords: Emigration -- Mzab -- Algérie

Islam and state expansion in Algeria: nineteenth-century Saharan frontiers - Holsinger, Donald C. (Islamism and secularism in North Africa, 1994)
Keywords: Emigration -- Mzab -- Algérie

Migration interne et classes moyennes en Algérie : le cas des Mozabites - Holsinger, Donald C. (Les Classes moyennes au Maghreb: ouvrage collectif, 1980)
Keywords: Emigration -- Mzab -- Algérie

Une lettre des Mozabites d'Alger en 1848 - Emerit, Marcel (Bulletin de Liaison Saharienne, 1953)
Keywords: Emigration -- Mzab -- Algérie

L'émigration temporaire des M'zabites dans les villes du Tell algérien - Vigourous, L. (La France méditerranéenne et africaine, 1939)
Keywords: Emigration -- Mzab -- Algérie

L'émigration mozabites dans les villes du Tell algérien - Vigourous, L. (Travaux de l'Institut de Recherches Sahariennes, 1945)
Keywords: Emigration -- Mzab -- Algérie

Effects of the transition from the Turkish and the French Regime in Algiers : the case of the Mzabi Talaba (Tolba) - Hoexter, Miriam (Asian and African Studies, 1983)
The purpose of this paper is to find out how and in what ways French policy, during and after the corporative (Barrāniyya) phase (until 1868), affected the traditional position and functions of the Mīzābī Ṭalaba in Algiers. I.a. based on documents in the French National Archives in Paris and in Les Archives du Gouvernement Général de l’Algérie, Aix-en-Provence.
Keywords: Emigration -- Mzab -- Algérie

L'émigration temporaire des mozabites dans les villes du tell Algérien - Vigourous, L. (Centre des hautes études sur l'Afrique et l'Asie moderne, 1941)
Keywords: Emigration -- Mzab -- Algérie